Pengaruh Struktur Modal, Likuiditas Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Sub Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Suci Imelda; Dian Ayu Andriani (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to determine the Effect of Capital Structure, Liquidity, and Profitability on Stock Prices in Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange for the period 2022-2024. The analysis technique used multiple linear regression analysis. The results showed that DER, CR, and ROA simultaneously had no effect on stock prices with F count > F table (1.963 > 2.85) and a significance level of 0.136 > 0.05. DER partially has no effect on stock prices with t count 1.409 ˃ t table 2.024 and significant 0.167 > 0.05. CR partially has an effect and is significant on stock prices with a t count -2.147 < t table 2.024 and significant 0.038 < 0.05. ROA variables partially have no effect and are significant on stock prices with t count -0.148 ˃ t table 2.024 and significant 0.883 > 0.05. Based on the coefficient of determination, it shows the influence of the three independent variables on stock prices by 13.4% while the remaining 86.6% is influenced by other factors outside the study.